2021
DOI: 10.1016/j.vaccine.2020.06.082
|View full text |Cite
|
Sign up to set email alerts
|

A global agenda for older adult immunization in the COVID-19 era: A roadmap for action

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 75 publications
0
64
0
1
Order By: Relevance
“…The recent introduction and rollout of the pneumococcal conjugate vaccine and rotavirus vaccine have shown that new vaccines can be successfully rolled out within existing public health infrastructure ( Malik et al, 2019 ). While a clear strategy for childhood vaccination exists globally and in India, a blueprint for adult immunization is recognizably inadequate and is being increasingly acknowledged as important for sustaining and enhancing health outcomes ( Privor-Dumm et al, 2020 ). So far, India has initiated the process of targeting adults by setting up of health centers adult and immunization as an example of a life course approach to health services ( Lahariya and Bhardwaj, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction and rollout of the pneumococcal conjugate vaccine and rotavirus vaccine have shown that new vaccines can be successfully rolled out within existing public health infrastructure ( Malik et al, 2019 ). While a clear strategy for childhood vaccination exists globally and in India, a blueprint for adult immunization is recognizably inadequate and is being increasingly acknowledged as important for sustaining and enhancing health outcomes ( Privor-Dumm et al, 2020 ). So far, India has initiated the process of targeting adults by setting up of health centers adult and immunization as an example of a life course approach to health services ( Lahariya and Bhardwaj, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results from Brazil indicated a significantly lower odds of needing intensive care treatment, invasive respiratory support and death among patients with SARS-CoV-2 that received the inactivated trivalent influenza vaccine 27. The International Council on Adult Immunization highlights in their roadmap that influenza, pneumococcal and herpes zoster vaccines programmes are more urgent than ever before 28 . As a further potential implication on influenza vaccination, if there is a competitive effect between influenza and SARS-CoV-2, this effect may also be seen with live attenuated influenza vaccination (LAIV) which if offered to children in England and could in turn have a role in outbreak management.…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction and rollout of the pneumococcal conjugate vaccine and rotavirus vaccine have shown that new vaccines can be successfully rolled out within existing public health infrastructure (Malik et al 2019). While a clear strategy for childhood vaccination exists globally and in India, a blueprint for adult immunization is recognizably inadequate and is being increasingly acknowledged as important for sustaining and enhancing health outcomes, as well as social and economic outcomes (Privor-Dumm et al 2020b). The framework for vaccine delivery for older adults depends on factors such as availability of evidence, existing vaccination policies, political will, robust surveillance systems, funding allocation, and importantly, communication and public messaging (Privor-Dumm et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Privor-Dumm et al 2020b). The framework for vaccine delivery for older adults depends on factors such as availability of evidence, existing vaccination policies, political will, robust surveillance systems, funding allocation, and importantly, communication and public messaging(Privor-Dumm et al 2020a).…”
mentioning
confidence: 99%